Dart 1 for everyone fast, flexible, structured code for the modern web - Strom, Chris (Pragmatic programmers, 2014)
Completely updated for Dart 1 and the ECMA standard, with new sections on new Dart features like method cascades, event streams, and class constructor syntax, this book wastes no time in immersing you in the finer points of this powerful and surprisingly beautiful language.